2018
DOI: 10.1089/pho.2017.4326
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence Analysis of Antibacterial Photodynamic Therapy Using Methylene Blue Mediated by Low-Intensity Level Laser Against Cariogenic Biofilms

Abstract: This study demonstrated that aPDT has promising potential to be used as an additional method to control oral cariogenic biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The systematic review showed that among the cariogenic microorganisms listed in the selected studies, the most studied microorganism was Streptococcus mutans (82%) [12,14,15,16,17,18,19,20,21,23,24,25,26,27,28,29,31,32,33,34,35,37,39,40,41,42,43,45].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic review showed that among the cariogenic microorganisms listed in the selected studies, the most studied microorganism was Streptococcus mutans (82%) [12,14,15,16,17,18,19,20,21,23,24,25,26,27,28,29,31,32,33,34,35,37,39,40,41,42,43,45].…”
Section: Resultsmentioning
confidence: 99%
“…The success of PDT depends on factors such as the administrated dose of light in the target cells and the time of exposure to light [46]. Considering these factors, we found that the most widely used light source was the red LED (32%) with wavelengths ranging from 625 to 670 nm [12,15,16,17,18,21,24,29,30,32,36,40], the most commonly used PS was methylene blue [13,16,18,21,23,24,27,28,29,30,32,33,36,38,39,42], and the most widely used pre-irradiation time was 5 min [12,14,15,16,17,19,20,21,22,27,28,30,31,32,33,39,42,43,45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photosensitizer SAPYR (2-((4-pyridinyl)methyl)-1H-phenalen-1-one chloride) destroyed bacteria, embedded in extracellular polymeric substance to an extent that is regarded as disinfection [38]. In addition, methylene blue in combination with a low-intensity laser was successfully used to control cariogenic-like biofilms formed by Streptococcus mutans [40].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that antimicrobial photodynamic therapy (aPDT), have also been developed for the treatment of dental caries. [22–27] The photodynamic action occurs when a photosensitizing agent absorbs photons from the light source and its electrons enter an excited singlet state. [28] Different classes of chemical compounds, such as phenothiazines, phthalocyanines, and porphyrins, which have photoactive properties, have been effective in aPDT.…”
Section: Introductionmentioning
confidence: 99%